Program Pelatihan Jurnalistik Sekolah di MA NU Tengguli Kecamatan Bangsri Kabupaten Jepara - Murniati Murniati; Khoirul Muslimin; Abdul Wahab; Mahfudlah Fajrie (Journal of Dedicators Community, 2019)
The journalistic school service activities were carried out at MA NU Tengguli. This school has students who have the potential to write, both writing short stories, poetry, and poetry but are not structured and do not meet the standard rules of writing. Besides the ability to write news or opinions and articles not yet seen. The aim of this services is to increase the journalism skill of the students there. Based on the analysis, the activities carried out are 1) News writing training; 2) Training on making press releases; 3) Training on layout and editing of scripts. The results obtained are 1) Students are able to arrange interview questions and write in the form of reportage; 2) students are able to make news; 3) students are able to make press releases and understand the functions of public relations; 4) students are able to make simple layouts for wall magazines and do editing of scripts.